Política de educação especial: um estudo comparado crítico entre Brasil e Portugal - Ribeiro, Érika Rosa Rodrigues (2024)
The present work aims to analyze, through a critical comparative study, the educational policy of Brazil and Portugal, based on special education legislation, highlighting the similarities and speci-ficities that mark the regulations of these two countries, having as reference the main political documents that mark the trajectory of these nations. The analysis was anchored in studies by Gramsci (1999), which make it possible to understand the political and economic determinants that involve the pedagogical discourse of political texts and documents. As a reference in the area of special education, we will dialogue with the studies of Jannuzzi (2004), to discuss the relationship between special education policies and the historical and social context. We advance the discus-sion with the contextualization of the guidelines and regulations in the two education systems, in order to elucidate the trajectories of educational policies. We used as a reference the studies by Sobrinho, Sá, Pantaleão and Jesus (2015) on international comparative research and reflections on public policies, by Shiroma, Morais and Evangelista (2007), Shiroma, Campos and Garcia (2004), with the purpose of producing a critical qualitative study on special education in Brazil and Portu-gal. To develop the work, official documents and data made available by the Brazilian Ministry of Education and the Directorate-General of Education of Portugal were consulted. The analysis of educational policies permeated the social, historical and cultural contexts of the constitution of special education in both nations. Among the results obtained by the research, it is worth highlight-ing the fact that special education policies in the countries analyzed are close and distant. As points of contact: a historical trajectory of the school system, which went through exclusion, inte-gration, philanthropy and is currently considered inclusive; dialogue with international movements and declarations, especially UNESCO; the development of individual planning to serve the target student of inclusive education. Taking as a reference the current documents from Brazil and Portu-gal, the Special Education Policy from the Perspective of Inclusive Education of 2008 and Decree-Law No. 54/2018, we highlight as distancing aspects: the methodological focus of the Portuguese document, from the perspective of a multilevel and universal learning design, which universalizes the way in which specialized educational service work must be carried out, while in the Brazilian case, the focus is on the specialized educational service service, and the performance of the special education professional in the classroom resources and the diversity of applied methodologies, ac-cording to the specificities of the students served; and the way they identify the target audience for special education, in Brazil students with disabilities, giftedness and high abilities and disorders are considered, in the Portuguese document the target audience students for inclusive education are those with learning difficulties, whether due to disability issues or social, cultural and economic conditions.